2017
DOI: 10.21303/2504-5695.2017.00318
|View full text |Cite
|
Sign up to set email alerts
|

Study of Keeping Probiotic Properties of Sour-Cream Butter at Storage

Abstract: The aim of the work was the study of keeping probiotic properties of sour-milk butter with inclusion of Lactobacillus acidophilus La-5 (La-5) monoculture. Flora Danica mesophile culture independently (FD); in combination with La-5 and La-5 independently were used for fermenting cream. The output consistence of culture in cream was 1×106 CFU/cm3. In autumn-winter and spring-summer period of the year four butter groups were prepared, they differed by temperature of cream fermentation: I group – (30±1) ºС; II – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They found that the viability of the probiotic bacteria declined throughout the 22 days storage period, although cultures retained counts higher than 6 Log CFU/g, constituting, therefore, a good vehicle for delivering probiotic bacteria. Musi, Tsisary, Slyvk, Mykhaylytsk, and Gutyj (2017) report that cream fermentation with Flora Danica mesophilic culture plus Lactobacillus acidophilus , at 30°C, showed high viable cell counts. The shelf life of this sour‐cream butter with probiotic properties was 35 days at temperature of 0°C–5°C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…They found that the viability of the probiotic bacteria declined throughout the 22 days storage period, although cultures retained counts higher than 6 Log CFU/g, constituting, therefore, a good vehicle for delivering probiotic bacteria. Musi, Tsisary, Slyvk, Mykhaylytsk, and Gutyj (2017) report that cream fermentation with Flora Danica mesophilic culture plus Lactobacillus acidophilus , at 30°C, showed high viable cell counts. The shelf life of this sour‐cream butter with probiotic properties was 35 days at temperature of 0°C–5°C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To improve emulsifying and stabilizing properties, microparticulate protein (MPP) produced from milk is used, the microparticles of which have a regular spherical shape and a size from 1 to 10 microns, which corresponds to the parameters of fat globules in milk products. The introduction of MPP into low-fat sour cream made it possible to increase its water-holding ability and creaminess without increasing the fat content of the product at shear rate gradient values from 3 to 437.4 s -1 (Musiy et al, 2017). There is evidence that the increase in the sour cream's water-holding ability and its viscosity was facilitated by the addition of the ingredients of starch-and oil-containing plant raw materials: not fried buckwheat seeds (Evdokimov et al, 2010), leaf extract of Moringa oleifera or oil made of the said raw material (Salem et al, 2015).…”
Section: Introductionmentioning
confidence: 99%